Kandidias Oral pada Penderita Anemia Defisiensi Besi (Fe) dan Penetalaksanaannya - Sri Budiarti Wongsohardjono (Majalah Kedokteran Gigi Indonesia, 2012)
Background: Iron deficiency anemia is a microcytic anemia caused by chronic blood loss dueto such problems as excessive menstrual flow, gastrointestinal bleeding, gasterektomi or malabsorption that reduces the absorption of Fe. Predisposing factors that lead to the disruption of the ecology of oral candidiasis or oral microbiological changes can be due to malnutrition (iron deficiency, folic acid, vitamin B12) and the very old age. Objective: To report a case of iron deficiency anemia with oral candidiasis and its management. Case Report: A 69-year man in the reference by peer demonstrated swollen gums, mouth pain and difficulty in swallowing. A moth ago he was hospitalized and boarded for a week but no change, his body weight loss was 25kg. paleconjunctiva and face, droliing, looked weak. The body temperature was 370 C; the BP measurement was: 125/80mmHg; with body weight was 50kg; right and left submandibular  lymph nodes become enlarging and soreness palpatiom. Symmetrical face. Right and left lip corners are angular kheilitis, cheek mucosa, palate hyperemia, gingival stipling was disappeared, hyperemia, dorsal surface smooth tongue, hyperemia, depapilasi, OHI: bad; thick saliva, hypersalivation. A lot of dental caries and the remaining roots. Management: Examination of the saliva with KOH solution looked a hyphe. Routine blood tests and profile of fe all within normal limits except RBC was 3,37.106 / uL; HGB: 11.0 g / dl; HCT: 32.2%, Fe 29.00 u g / dl (below normal). Treatment with 3% perhidrol mouthwash, Nyistatin solution 3 x daily. Zegase tablet 2x daily. Paracetamol tablets if necessary. Conclusion sixteen days later the patient recovered.